Proses Asuhan Gizi Terstandar pada Pasien Anemia dengan AKI dd ACKD, Suspek Sepsis, Wound Dehisensi dd Fistula Enterokutan: Laporan Kasus - Alfi Miftahul Nikmah; Dwi Sarbini; Agus Prastowo (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Introduction: Acute Kidney Injury (AKI) is a sudden decline in kidney function, whereas Acute on Chronic Kidney Disease (ACKD) refers to an acute deterioration superimposed on pre-existing chronic kidney disease. Both conditions are associated with high mortality rates, especially when accompanied by other complications such as sepsis and postoperative conditions. Wound dehiscence is a postoperative complication characterized by the reopening of a surgical wound. This risk increases in patients with compromised immune status, sepsis, and chronic illnesses such as Chronic Kidney Disease (CKD). The aim of this case study is to provide nutritional care for a patient with Acute Kidney Injury (AKI) differential diagnosis of Acute on Chronic Kidney Disease (ACKD), suspected sepsis, wound dehiscence, suspected enterocutaneous fistula, and anemia, tailored to the patient’s clinical condition and nutritional needs. Case Presentation: An 18-year-old female student, referred to as Patient A, was diagnosed with Acute Kidney Injury (AKI) dd Acute on Chronic Kidney Disease (ACKD), suspected sepsis, wound dehiscence, suspected enterocutaneous fistula, and anemia. The patient had undergone exploratory laparotomy due to perforated appendicitis. Conclusion: The nutritional intervention provided was effective in improving the nutritional status of the patient with Acute Kidney Injury (AKI) dd Acute on Chronic Kidney Disease (ACKD), suspected sepsis, wound dehiscence, suspected enterocutaneous fistula, and anemia.